The Implementation of Guided Discovery Learning Method Towards Science Process and Students' Creative Thinking Ability on Fungus Material - Khairunisa, Nisrina; Bintari, Siti Harnina; Mubarok, Ibnul (FMIPA UNNES, 2021)
Learning on 21 centuries is not only focused on improving students' learning achievement but also focused on developing students' skills and abilities. One of them is to develop the students' science process and creative thinking skills. Guided discovery is one of the learning methods that is suggested for showing those students' skills. This research is aimed to know the result of achievement on students’ science process and creative thinking skills on fungus material. The method used was pre-experimental by using a One group pre-test post-test design to conduct the research. The population of the research was all students of class X MIPA SMAN 8 Semarang in the academic year 2019/2020. The sample of the research used the purposive sampling technique. The result found that students’ science process skills in this research showed the result of each aspect got very good criteria in two experimental classes. The result of students’ creative thinking got classical achievement that was 94.36% by the number of students that reached it was 67 students of 71 sample. The improvement in students’ creative thinking result got an improvement by N-gain score 0,73 with high criteria. Based on the result of analysing the research, it can be concluded that the Guided Discovery learning method can improve students’ achievement of the science process and creative thinking skills.